PELATIHAN USAHA KAWASAN PARIWISATA DI DESA TULUS BESAR, KECAMATAN TUMPANG, KABUPATEN MALANG - Hilda Cahyani; Nadia Hanayeen; Alvin Nouval; Mariana Ulfah Hoesny; Sugeng Hariyanto (P3M Politeknik Negeri Malang, 2024)
This community service is aimed at accommodating the needs of the Tulus Besar village community, Tumpang District in improving the ability to manage natural tourist attractions and the potential of tourist villages in the Tulus Besar tourist village area by involving tourism business actors (travel agents) to increase tourist visits, both local and foreign. Participants in this training are tourism business actors in Tulus Besar village. Through this activity, it is hoped that there will be an increase in the economic value of tourism and arts potential as well as the quality of human resources for the managers of the tourist village through increasing the ability to manage tourist attractions and tourist villages owned by the Tulus Besar village community. This activity was carried out in five stages, namely planning (to find out the number of participants who are involved and the materials needed for the training), coordination to do a survey, survey with village officials and travel agents (to ensure the plans made are by needs), Focus Group Discussion, monitoring and evaluation (giving questionnaires to training participants regarding training implementation and materials).